THE INFLUENCE OF COMPANY SIZE, AUDIT OPINION, PROFITABILITY AND SOLVENCY ON AUDIT DELAY (CASE STUDY ON A CIGARETTE COMPANY LISTED ON THE INDONESIAN STOCK EXCHANGE) - Yanti, Amalia Dwi; Astuty, Widia (Proceeding International Seminar of Islamic Studies, 2024)
The Influence of Company Size, Audit Opinion, Profitability and Solvency on Audit Delay (Case Study of a Cigarette Company Listed on the Indonesian Stock Exchange). This research aims to determine the influence of company size, audit opinion, profitability and solvency on audit delay. This research was conducted on 5 cigarette companies listed on the Indonesia Stock Exchange (BEI) during the 2017-2022 period using secondary data collection methods, namely the companies' annual financial reports. The number of samples obtained in 6 years was 30 observations using the purposive sampling method. The independent variables in this research are company size, audit opinion, profitability and solvency. The dependent variable is audit delay. The method used in this research uses multiple linear regression analysis. The research results show that partially profitability has no significant effect on audit delay, while company size and solvency have a significant effect on audit delay in a positive direction and audit opinion has a significant effect on audit delay in a negative direction. Simultaneously, company size, audit opinion, profitability and solvency have a significant effect on audit delay.